(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
In this study, we aimed to determine the impact of flipped classroom, blended learning and traditional methods on student self-regulation skills and computer self-efficacy perceptions. A total of 119 students constituted the working group of research who are attending Science Education, Turkish Education and Primary Education departments at Kilis 7 Aralık University Muallim Rifat Faculty of Education in the fall term of 2017-2018 academic years. Within the scope of the research, three groups were formed; two of them were experimental and one was control group. Flipped classroom was used in experimental group-I, blended learning method was used in experimental group-II and traditional approach was used in control group. "Computer self-efficacy scale" and "self-regulation scale" have been used for data collection tools which have been applied to the students. Descriptive statistics, t-test and one-way ANOVA were used to analyze the obtained data. There was no significant difference between the computer self-efficacy perceptions and self-regulation skills of the students in experiment-I, experiment-II and control groups after nine weeks of research. It has also been found that the flipped classroom has a positive effect on students’ self-regulation skills.